Peripheral nerve involvement at first diagnosis of multiple sclerosis: a prospective MR neurography study - Fösleitner, Olivia; Jäger, Laura Bettina; Schwarz, Daniel; Hayes, Jennifer; Sam, Georges; Wildemann, Brigitte; Wick, Wolfgang; Bendszus, Martin; Heiland, Sabine (Investigative radiology, 2023)
Objectives - The aim of this study was to assess peripheral nerve involvement in patients with multiple sclerosis (MS) at first clinical presentation using quantitative magnetic resonance (MR) neurography in correlation with clinical, laboratory, electrophysiological, and central nervous MR imaging data. - Materials and Methods - In this prospective monocentric study, 30 patients first diagnosed with MS according to the McDonald criteria (19 women; mean age, 32.4 ± 8.8 years) and 30 age- and sex-matched healthy volunteers were examined with high-resolution 3 T MR neurography using a dual-echo T2-relaxometry sequence covering the tibial and peroneal nerves from proximal thigh to distal calf. Magnetic resonance biomarkers of T2 relaxation time (T2app), proton spin density (PSD), and nerve cross-sectional area (CSA) were correlated with clinical symptoms, intrathecal immunoglobulin (Ig) synthesis, nerve conduction study, and lesion load on brain and spine MR imaging. The diagnostic accuracy of MR biomarkers was assessed using receiver-operating characteristic curves. - Results - Diffuse nerve changes were detected along the tibial and peroneal nerves in MS patients, who showed decreased PSD (P < 0.001), increased T2app (P < 0.001), and smaller tibial nerve CSA (P < 0.001) compared with healthy subjects. Tibial PSD was identified as best parameter separating patients from controls (area under the curve = 0.876). Intrathecal IgG and IgM synthesis correlated with PSD values (r = −0.44, P = 0.016, and r = −0.42, P = 0.022). Contrast-enhancement of brain or spine lesions was related to larger tibial and peroneal CSA (P < 0.001, P = 0.033). Abnormal electrophysiology correlated with higher tibial and peroneal T2app (P < 0.001 and P = 0.033), lower tibial and peroneal PSD (P = 0.018 and P = 0.002), and smaller peroneal CSA (P < 0.001). - Conclusions - Quantitative MR neurography reveals peripheral nerve changes in patients with initial diagnosis of MS. Correlation of imaging findings with intrathecal immunoglobulin synthesis may indicate a primary coaffection of the peripheral nervous system in MS.